2018
DOI: 10.1136/bcr-2018-224259
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive myxoinflammatory fibroblastic sarcoma with multiple site metastases

Abstract: Myxoinflammatory fibroblastic sarcoma (MIFS) is a rare soft tissue sarcoma which was initially observed in acral sites and characterised by spindle cells, pleomorphic bizarre cells and distinctive large Reed-Sternberg-like cells admixed with an intense inflammatory cell infiltrates. MIFS manifests as a slow growing often superficial lesion which can be mistaken as infectious or chronic inflammatory process or benign tumours such as nodular fasciitis, giant cell tumour of tendon sheath or synovial pseudocyst. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“… 2 Clinical symptoms resemble benign tumors, ganglion cyst, lipoma, fibroma, and inflammatory processes. 3 , 4 , 5 Some cases of MIFS have been reported in uncommon sites including the upper back, scapula, head, and cervicothoracic region. 2 , 4 , 6 , 7 Etiologic causes and risk factors are unknown.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 2 Clinical symptoms resemble benign tumors, ganglion cyst, lipoma, fibroma, and inflammatory processes. 3 , 4 , 5 Some cases of MIFS have been reported in uncommon sites including the upper back, scapula, head, and cervicothoracic region. 2 , 4 , 6 , 7 Etiologic causes and risk factors are unknown.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 , 5 Some cases of MIFS have been reported in uncommon sites including the upper back, scapula, head, and cervicothoracic region. 2 , 4 , 6 , 7 Etiologic causes and risk factors are unknown. Only one study has reported a history of renal transplantation in one case.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations